2020
DOI: 10.1055/s-0040-1713621
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Traumatic Encephalopathy: Advocacy and Communicating with the Public

Abstract: Over the past 40 years, advocacy groups have been instrumental in raising awareness for neurodegenerative diseases such as Alzheimer's disease. More recently, advocates have emerged to educate about sports concussions and chronic traumatic encephalopathy (CTE), including the Concussion Legacy Foundation (CLF). CTE is a neurodegenerative disease caused in part by repetitive head impacts (RHI). While the majority of CTE research has focused on studying former American football players, CTE has also been found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This coincides with consensus confirmation of the CTE pathognomonic lesion and publication of the NINDS pathological criteria [ 58 ]. It further correlates with the increase in postmortem brain donations to the VA-BU-CLF brain bank due to increased efforts to promote brain donation by the CLF, including the relaunch of the brain donation campaign and a transition to an online signup system [ 86 ]. Assessment of the 42 tissue studies indicated that the CTE cases were sourced from at least 13 different brain banks.…”
Section: Resultsmentioning
confidence: 99%
“…This coincides with consensus confirmation of the CTE pathognomonic lesion and publication of the NINDS pathological criteria [ 58 ]. It further correlates with the increase in postmortem brain donations to the VA-BU-CLF brain bank due to increased efforts to promote brain donation by the CLF, including the relaunch of the brain donation campaign and a transition to an online signup system [ 86 ]. Assessment of the 42 tissue studies indicated that the CTE cases were sourced from at least 13 different brain banks.…”
Section: Resultsmentioning
confidence: 99%
“…CTE can only be officially diagnosed upon post-mortem analysis. The pathognomonic lesions for this disease are perivascular, hyperphosphorylated tau-immunoreactive neurofibrillary tangles and abnormal neurites distributed at the sulcal depths [ 60 , 61 ]. Though it may not be officially diagnosed while patients are alive, there are clinical characteristics that when paired with a patient’s history, can strongly indicate CTE.…”
Section: Outcomes Of Tbi Due To Domestic Violencementioning
confidence: 99%
“…Though it may not be officially diagnosed while patients are alive, there are clinical characteristics that when paired with a patient’s history, can strongly indicate CTE. CTE is a progressive disease, with most patients not showing symptoms until years or decades after their head injuries [ 59 , 60 ]. Patient with CTE may exhibit childish behavior, including violent and disinhibited outbursts.…”
Section: Outcomes Of Tbi Due To Domestic Violencementioning
confidence: 99%
“…In recent decades, there has been an increase in research on sport-associated concussion as a result of neurological symptoms experienced by high-profile and retired athletes, consequently lawsuits with large media coverage have ensued. Studies have linked repeated incidence of concussive events with some neurological conditions such as chronic traumatic encephalopathy (CTE) ( 1 ). This profound link clearly indicates the importance for researchers into the acute and chronic effects of concussion to make participation in sport safer for both professional and amateur/community athletes during their playing careers and beyond.…”
Section: Introductionmentioning
confidence: 99%